The Impact of Quarterly Earnings Announcements on Stock Prices - Patryk Jagliński (Nauki o Finansach)
The post-earnings-announcement-drift (PEAD) is a long-standing market anomaly that is in conflict with the semi-strong form of market efficiency. The main aim of the article was to investigate how investors react to quarterly earnings announcements and to find out if the anomaly is present on the Warsaw Stock Exchange. An event study analysis for the period of 2017-2019 was conducted to answer these questions. Contrary to most other studies concerning the topic, no evidence was found for the existence of PEAD in the group of companies that reported earnings above the market expectations. The anomaly was only spotted in the group of companies that underachieved earnings forecasts. The author's concluding supposition is that the existence of the anomaly in the latter group is most likely due to the fact that short-selling is not widely available on the Polish stock exchange, and if the market participants had the tools necessary to counteract the anomaly, i.e. the possibility to take on short positions, it would not be present.(original abstract)